Hyperuricemia – a warning signal for prediabetes? - D.LAKSHMI LALITHA,; B.SREEHARI BABU,; DSSK RAJU, (International Journal of Pharma and Bio Sciences, 2017)
With an objective to study the effect of high uric acid levels on insulin resistance, a total of 100 subjects were categorized into two groups (Group A and Group B) based on their serum uric acid levels. They were investigated for fasting plasma glucose, insulin and HbA1c. HOMA-IR was calculated basing on plasma glucose and insulin. Fasting plasma glucose, insulin and HbA1c levels showed an increase in Group B subjects when compared to Group A. HOMA –IR which is the indicator for insulin resistance also showed an increase in Group B subjects when compared to Group A. This increase is statistically significant (p<0.001). The beneficial effect of uric acid as an antioxidant is challenged by its abnormal concentration in the serum. This may lead to prediabetes which, over a period of time, might progress to frank diabetes. Thus serum uric acid level can act as a warning signal for future onset of diabetes.